2021
DOI: 10.1101/2021.03.19.436149
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Catchet-MS identifies IKZF1-targeting Thalidomide analogues as novel HIV-1 latency reversal agents

Abstract: A major pharmacological strategy toward HIV cure aims to reverse latency in infected cells as a first step leading to their elimination. While the unbiased identification of molecular targets physically associated with the latent HIV-1 provirus would be highly valuable to unravel the molecular correlates of HIV-1 transcriptional repression and latency reversal, due to technical limitations, this has not been possible. Here we use dCas9 targeted chromatin and histone enrichment strategy coupled to mass spectrom… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 99 publications
(164 reference statements)
1
7
0
Order By: Relevance
“…Strategies that use combinatorial approaches of LRAs could result in higher efficacy in reactivating HIV-1 latency (5). We have shown in previous studies that the effect of pyrimethamine on HIV-1 latency ex vivo could be potentiated when combined with other LRAs including HDACi (44,46). We therefore designed the study to include a combinatorial arm to test whether the effect of the individual LRAs could be potentiated in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Strategies that use combinatorial approaches of LRAs could result in higher efficacy in reactivating HIV-1 latency (5). We have shown in previous studies that the effect of pyrimethamine on HIV-1 latency ex vivo could be potentiated when combined with other LRAs including HDACi (44,46). We therefore designed the study to include a combinatorial arm to test whether the effect of the individual LRAs could be potentiated in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Our preclinical studies identified BRG-Brahma Associated Factors (BAF) complex inhibitors (BAFi) as a novel LRA class which we demonstrated enhanced the activity of other LRA classes (44)(45)(46). The BAF (mammalian SWI/SNF) chromatin remodeling complex is a key repressor of HIV-1 latency that uses ATP hydrolysis to position repressive nucleosome nuc-1 at the HIV-1 long terminal repeat, causing transcriptional silencing of HIV-1 gene expression thereby maintaining HIV-1 latency (47,48).…”
Section: Introductionmentioning
confidence: 98%
“…In a previous study 16 , we identified putative latent promoter-bound regulators of HIV-1 gene expression by dCas9-targeted chromatin immunoprecipitation coupled to mass spectrometry (Catchet-MS) (Figure 1A). Because of differential enrichment at the latent HIV-1 and inactive LTR, we hypothesized that these factors may contribute to the maintenance of HIV-1 latency as putative repressors of HIV-1 gene expression.…”
Section: Pcid2 Is An Hiv-1 Ltr-bound Latency Promoting Factormentioning
confidence: 99%
“…In latent cells, and consistent with literature, there is a basal level of residual transcription and basal expression of GFP 31 (Figure 3C-D), with about 37.7% (mean) of GFP+ cells also expressing vRNA (Figure 3E). To demonstrate the effect of a release in a transcriptional block specifically, we performed FISH-Flow in J-Lat 11.1 cells shRNA depleted of Ikaros zinc finger 1 (IKZF1), a recently identified HIV-1 transcriptional repressor 16 . Indeed, we observed strong viral reactivation in IKZF1-knockdown cells as shown by a marked increase in vRNA and GFP producing cells (Figure 3D), of which 48.6% (mean) also express vRNA (Figure 3E).…”
Section: Pcid2 Is An Hiv-1 Ltr-bound Latency Promoting Factormentioning
confidence: 99%
See 1 more Smart Citation